2011
DOI: 10.3846/13923730.2011.619325
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Multiple Tuned Mass Dampers for the Wind Excited Benchmark Building / Optimalūs Masės Slopintuvai Vėjo Veikiamuose Aukštybiniuose Pastatuose

Abstract: Abstract. The performance of multiple tuned mass dampers (MTMD) installed at the top floor of the wind excited benchmark building under across wind loads is investigated. The performance of MTMD is compared with that of single tuned mass damper (TMD) having same total mass. The governing equations of motion of the building with MTMD/ TMD are solved by employing state space formulation. Initially, the TMD is installed at the top floor of the benchmark building and the optimum parameters of the damper for the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 20 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Patil and Jangid studied the optimum parameters of the MTMDs for reducing the dynamic response of a wind‐excited benchmark building. They found that the MTMDs are quite effective and robust in the vibration control of the benchmark buildings as compared with the STMD.…”
Section: Introductionmentioning
confidence: 99%
“…Patil and Jangid studied the optimum parameters of the MTMDs for reducing the dynamic response of a wind‐excited benchmark building. They found that the MTMDs are quite effective and robust in the vibration control of the benchmark buildings as compared with the STMD.…”
Section: Introductionmentioning
confidence: 99%
“…e structure considered in this study is a 76-story benchmark building, which is very sensitive to wind [33][34][35][36]. Detailed information of the building can be found in reference [33,35].…”
Section: Benchmark Building With/without Tmdsmentioning
confidence: 99%
“…A single tuned mass damper placed at the top of the building is denoted as STMD and is shown in Figure 1 Optimum design of STMD for wind and earthquake response mitigation is different [35,37]. Patil and Jangid [36] proposed a robust procedure to estimate optimal parameters of TMDs for wind-sensitive structures. Sadek et al [38] provided optimal parameters of TMDs for earthquake-induced vibration control.…”
Section: Benchmark Building With/without Tmdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the common aerodynamic design include the modification of the corner geometry of a building, the addition of openings to a building, and the control of the building aspect ratio. The second method generally employed to reduce the wind-induced responses of high-rise buildings is associated with the use of additional damping devices such as viscoelasticity dampers, fluid dampers, tuned liquid dampers, and tuned mass dampers (Lewandowski, Grzymislawska 2009;Patil, Jangid 2011). For structural engineers, both of the aforementioned methods are not always considered as a practical and feasible solution, since the decision to change the shape of a building and to use additional damping devices cannot be made by the structural engineer alone but instead require the consent of the owner and the architect.…”
Section: Introductionmentioning
confidence: 99%